Drug stewardship in chronic kidney disease to achieve effective and safe medication use. - KAZANCIOĞLU, RÜMEYZA; Hall R. K.; Kazancıoğlu R.; Thanachayanont T.; Wong G.; Sabanayagam D.; Battistella M.; Ahmed S. B.; Inker L. A.; Barreto E. F.; Fu E. L.; et al. (My University, 2024)
People living with chronic kidney disease (CKD) often experience multimorbidity and require polypharmacy. Kidney dysfunction can also alter the pharmacokinetics and pharmacodynamics of medications, which can modify their risks and benefits; the extent of these changes is not well understood for all situations or medications. The principle of drug stewardship is aimed at maximizing medication safety and effectiveness in a population of patients through a variety of processes including medication reconciliation, medication selection, dose adjustment, monitoring for effectiveness and safety, and discontinuation (deprescribing) when no longer necessary. This Review is aimed at serving as a resource for achieving optimal drug stewardship for patients with CKD. We describe special considerations for medication use during pregnancy and lactation, during acute illness and in patients with cancer, as well as guidance for the responsible use of over-the-counter drugs, herbal remedies, supplements and sick-day rules. We also highlight inequities in medication access worldwide and suggest policies to improve access to quality and essential medications for all persons with CKD. Further strategies to promote drug stewardship include patient education and engagement, the use of digital health tools, shared decision-making and collaboration within interdisciplinary teams. Throughout, we position the person with CKD at the centre of all drug stewardship efforts.